Theoretical energy yield of GaAs-on-Si tandem solar cells. Issue 1638 (13th February 2014) - Liu, Haohui; Ren, Zekun; Liu, Zhe; Brandt, Riley E.; Mailoa, Jonathan P.; Siah, Sin Cheng; Aberle, Armin G.; Buonassisi, Tonio; Peters, Ian Marius
ABSTRACT: III-V on Si multijunction solar cells represent an alternative to traditional compound III-V multijunction cells as a promising way to achieve high efficiencies. A theoretical study on the energy yield of GaAs/Si tandem solar cells is performed to assess the performance potential and sensitivity to spectral variations. Recorded time-dependent spectral irradiance data in two locations (Singapore and Denver) were used. We found that a 4-terminal contact scheme with thick top cell confers distinctive advantages over a 2-terminal scheme, giving a yield potential 21% higher than the 2-terminal scheme in Singapore and 17% higher in Denver. The theoretical energy yield benefit of a 4-terminal device emphasizes the need for further technology development in this design space.